An Investigation into the Effect of Concept Mapping on Students’ Learning Outcomes in Photosynthesis at the Senior High School Level - Owusu-Amponsem, George; Sam, Comfort Korkor; Ngman-Wara, Ernest Immaare Dare (European Scientific Journal, ESJ, 2026)
This study investigated the effect of concept mapping on senior high school students’ learning outcomes in photosynthesis in the Tolon District of Ghana. A quasi-experimental non-equivalent group design was employed, involving 80 Form 3 Biology students selected through simple random sampling. Students were assigned to experimental and control groups and taught using concept mapping and conventional methods, respectively. The results showed no statistically significant difference between the experimental and control groups in students’ knowledge and understanding of photosynthesis (t(78) = .38, p = .702). For application of knowledge, the control group performed significantly better than the experimental group (t(78) = -2.23, p = .029). However, the experimental group demonstrated significantly higher practical skills in photosynthesis (t(78) = 4.42, p < .001). No significant gender differences were found across the measured outcomes. The findings suggest that concept mapping does not significantly enhance students’ conceptual knowledge or application of knowledge within a short instructional period but is effective in improving practical skills. It is therefore recommended that concept mapping be integrated into biology instruction primarily to strengthen students’ practical and process-oriented learning outcomes in photosynthesis.